US industrial outlook : prospects for over 350 manufacturing and service industries (US Department of Commerce. International TradeAdministration Washington DCUS, 1986)
Describes the US industrial economy and prospects for the future. Shows activity both in the US marketplace and in the world economy. Discusses industry trends in international trade, US international trade in services, and global trends in US trade. Provides economic data and objective analyses of specific industries.
Includes bibliographies